DIAGNOSING STUDENTS’ LEARNING DIFFICULTIES IN THE EYES OF INDONESIAN MATHEMATICS TEACHERS - Ariyadi Wijaya; Heri Retnawati; Wahyu Setyaningrum; Kazuhiro Aoyama; Sugiman Sugiman (Journal on Mathematics Education, 2019)
Teachers’ diagnostic practice on students-difficulties is one of the important steps in designing and managing classroom lessons. The purpose of this study was to explore teachers’ perception and practices regarding diagnosing students’ learning difficulties. The participants of the study were 28 Indonesian mathematics teachers of Junior High School. The data was collected through a Focus Group Discussion and a teacher questionnaire. The data were analyzed qualitatively to describe how the teachers perceive learning difficulties and how the teachers diagnosed students’ learning difficulties. The results of the analysis reveal that the teachers do not yet perform an in-depth diagnosis of students’ difficulties in learning mathematics. The teachers only focus on the mathematics topics and non-mathematical issues, instead of on students’ thinking process. The teachers also do not differentiate the diagnosis, evaluation, and prediction test. With regard to the strategies used by the teachers to diagnose students’ difficulties, analyzing students’ responses to tests was the majority. In this respect, observing students’ learning process during classroom activities is rarely done by the teachers in the purpose of diagnosing students’ learning difficulties. The results of the diagnosis are mainly used as the basis for remedial and drill and practices. The results imply that more support is needed for teachers to improve their competences particularly in diagnosing students’ thinking process difficulties when learning mathematics.